Literasi Finansial Dini: Sosialisasi dan Edukasi Budaya Menabung melalui Ekspresi Kreatif Poster - Anak Agung Sri Dewi; Ni Komang Putri Krisnayanti; Ni Kadek Lina Widiantari; I Dewa Gede Henya Natandra; I Kadek Dwi Sedana Putra (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Low levels of early financial literacy in Indonesia lead to unhealthy financial behaviour in the future. This study aims to evaluate the effectiveness of promoting a culture of saving through creative poster design amongst 52 pupils in Years 1 and 2 at SDN 1 Singapadu Tengah. Using a descriptive qualitative method, this Community Service Programme (KKN) activity comprised pre-education, education and evaluation stages, all centred on poster creation. The pre-education results showed that pupils’ understanding of the concept of a bank was still low (36% in Year 1; 77% in Year 2). However, following the education phase through poster visualisation, pupils’ understanding improved significantly. Pupils successfully represented the concept of saving in concrete terms through symbols such as piggy banks, coins and dream items. Based on Jean Piaget’s theory of cognitive development, the activity of drawing piggy banks, coins and dream items successfully transformed abstract concepts into concrete operational concepts through the process of dual coding. The integration of visual arts proved effective as a medium for financial literacy education and assessment, catalysing a proactive shift in attitude towards fostering a culture of saving from an early age.